Isolation And Molecular Identification Of Endophytic Fungi In Tigernuts (Cyperus Esculentus L.) - Arogundade, Femi Qudus; Olatoye Taye Tolulope (My University, 2023)
Tiger nuts (Cyperus esculentus Lativum) are highly valued for their sweet tubers and numerous health benefits. Like other plants, tiger nuts harbor a diverse community of endophytic microorganisms that contribute to plant survival, growth, and development. However, when tiger nut tubers are consumed raw, there is a potential for the transmission of endophytic fungi to humans. Understanding the diversity of endophytic fungi associated with tiger nuts is crucial to assess the potential consequences of their transfer to humans during tiger nut consumption. Therefore, this study aimed to isolate and identify endophytic fungi from fresh tiger nuts. Fresh tiger nut samples were obtained from three different towns in Osun State, namely Osogbo, Oyan, and Ikirun. After aseptic rinsing and crushing of the tiger nut tubers, endophytic fungi were cultured on Potato Dextrose Agar (PDA). The molecular identification of the isolated fungi was performed using Polymerase Chain Reaction (PCR) and sequencing analysis of the internal transcribed spacer (ITS) region of the fungi using universal primers. The obtained ITS sequences were then subjected to a BLAST search on the NCBI database for identification. Three fungi were successfully sequenced and identified in this study. They were found to share close identity with Saccharomyces cerevisiae isolate 27 (99.62%), Saccharomyces cerevisiae isolate B-NC-12-OZ03 (99.0%), and Candida tropicalis strain Pe1 (98.79%). The presence of Saccharomyces cerevisiae and Candida species is noteworthy, as they are relevant in fermentation processes. However, their presence as endophytes in tiger nut tubers may lead to negative fermentation or spoilage of the tubers. Furthermore, Candida tropicalis has been reported as a pathogen in individuals with compromised immune systems. This study provides valuable information on the potential endophytic fungi that can be isolated from tiger nuts. Further research is recommended to explore the roles of these endophytic fungi and their implications in tiger nut quality, safety, and fermentation processes. Understanding the interactions between endophytic fungi and tiger nuts will contribute to better management practices and ensure the safe consumption of this popular plant.
Keywords: Isolation; Molecular Identification; Tiger Nuts